Parijoto Fruit Extract Nanoparticles As Glucose-Lowering Agent In Vitro - Fania Putri Luhurningtyas (Jurnal Kesehatan Prima, 2020)
Parijoto fruit is an herbal that is the potential to be used for the treatment of lowering blood glucose. The active compound in parijoto fruit can decrease glucose levels is flavonoids. The use of natural materials is limit because of their low solubility. It often failed in the clinical phase. The solution to this problem is that the parijoto fruit extract is formulated in the form of nanoparticles using chitosan and STPP as encapsulate materials. This study aims to determine the activity of nano chitosan parijoto fruit extract (NPFE) as a glucose-lowering agent by applying nanoparticle technology. PFE was made by ionic gelation reaction by mixing extract chitosan solution of 0.2% concentration, and NaTPP concentration of 0.1%. The characteristic of NPFE was particle size, PdI, and % transmittance. The effect of a glucose-lowering agent of NPFE tested by the Nelson Somogyi method. The particle size of the NPFE result is 269.3 nm, PdI value is 0.372, and the percentage of transmittance is 99.397%. The glucose-lowering effect of NPFE was more significant (EC50 <2 ppm ) than parijoto fruit extract (EC50 48,750 ppm) and quercetin (EC50 6,831 ppm). Nano chitosan parijoto fruit extract affects a glucose-lowering agent.